Roots from the Archipelago : Proto-Alor etymologies in the context of Alor languages - Perono Cacciafoco, Francesco (2019)
This paper reconstructs 15 Papuan etymologies from nine languages belonging to the Alor-Pantar language family. It offers a systematic attempt of a comprehensive etymological reconstruction, in this specific linguistic context, based on an all-embracing comparative methodology. The analysis is developed, in this initial stage, on a number of common words from the respective languages. The paper aims to offer a sampling of etymological restitutions inherent in the Papuan languages of Alor, establishing an unbiased methodology potentially applicable in the study and reconstruction of the proto-lexicon of Alor-Pantar languages (pAP). Working on a case-by-case basis, but moving in the framework of a historical-linguistic methodology connecting the different etymological reconstructions, the paper tries to draft, for the first time, a new and reliable historical phonetics of the Papuan languages of Alor. Moreover, it analyzes the ‘target languages’ considering the geographical distribution of the different groups of speakers, highlighting language contact and language alignment phenomena.